Adivasi Marginality and the Vicissitudes of Violence in Rejina Marandi’s Becoming Me - Sayan Chatterjee (IAFOR Journal of Arts & Humanities)
Considered the earliest known inhabitants of the Indian sub-continent region, the Adivasis have been marginalized at the fringes of society for centuries. Their secluded and unique lifestyle has been primarily characterized by geospatial isolation and religious-linguistic divisions. Moreover, the withdrawal of these indigenous people from modern paradigms and values made them stand out as the perennial “other” for both the colonial rulers and mainstream Indian society. The issues regarding Adivasi identity and existence are even more complicated and nuanced in Northeast India since the politics of identity and belonging are more intense and layered in this region because of its multi-ethnic structure. The politicization of ethnicity as a means of “resistance” by the ethnic communities has reinforced the “indigenous/outsider” binary in the region, often resulting in widespread and multifaceted violence. However, it is important to note that this violence extends beyond the physical or subjective forms, and includes more subtle and inconspicuous forms of coercion that perpetuate relations of domination and exploitation. In this context, Rejina Marandi’s Becoming Me becomes a significant literary endeavor. As the inaugural fictional work in English by an Adivasi from the Northeast, the novel attempts to ventriloquize the collective Adivasi concerns and experiences specifically in Assam, and Northeast in general. Drawing on various theoretical frameworks, this paper, therefore, intends to analyze the portrayal of Adivasi marginality in Marandi’s novel, and how it produces a continuum of violence, leading to the loss of their identity and dignity.